Gusto ko nang lumaki! I want to be all grown up! - Malabed, Liwliwa (Lampara books, 2013)
"Buding is the youngest child. She is annoyed by her elder siblings. She is always being ordered around by them, and threatened by them a monster will seize her. One time, she is persuaded to trade her ice cream for a doll that transforms into a string bean. But her brothers have all but finished everything, including the cone, and still there is no doll. Buding really wants to be all grown up..."